Predictors of pain during oocyte retrieval - Yoon Frederiksen; Mimi Y. Mehlsen; Signe M. S. Matthiesen; Robert Zachariae; Hans Jakob Ingerslev (Taylor & Francis Group, 2017)
Introduction: Pain during oocyte retrieval remains prevalent despite detailed and specific pain management protocols. Exploring the role of psychosocial risk factors of pain during the oocyte retrieval could identify possible targets for prevention. The present study assessed pain prevalence and possible risk factors for experiencing extreme pain levels in a large cohort of women receiving assisted reproductive technologies (ART) treatment. Methods: Participants were 810 first attendees about to begin treatment with ART. The participants completed questionnaires at three time points: at their 21st day of the cycle, during the waiting time before the oocyte retrieval surgery and after the oocyte retrieval. Results: Fifty-one (6.9%) of the women reported the oocyte retrieval to be very or extremely painful. The results of a multiple logistic regression indicated that the significant predictors of high pain intensity, measured before the oocyte retrieval, were negative gynecological experiences and side effects of hormonal treatment. Variables measured after the oocyte retrieval associated with pain intensity were higher levels of anxiety during the oocyte retrieval, lower levels of perceived control and longer duration of the procedure. Discussion: The findings of the present study may help to identify those women who are at increased risk of experiencing unacceptable pain levels during oocyte retrieval procedures and the medical staff is advised to take psychological factors into account.